Autism, Art and the World Behind the World: Adventures in Neurodiverse Communication. - White, Brent; Boue, Sonia (Disability Studies Quarterly, 2015)
Pioneering autistic, neurodiverse language and communication styles the author’s explore the poetic potency of non-linear and non-verbal phenomena in neurodiverse interpersonal relationships. In doing so, they allow the linear thinker to experience challenge in reading, for which equivalencies can be sought in the challenges of social pragmatics for autistics. Within this experience of challenge the authors suggest the possibility of new empathic encounters with autistic and neurodiverse minds for a neurotypical readership. The authors further allow for autistic and neurodiverse readers to find reflections of difference with the potential to enable and empower. The use of social media comment facilities to provide meeting points, which may not be possible in real time, are also posited as access. Equivalences are sought across neurological difference which invite the reader to engage with a ‘stepping into’ of new cognitive and sensory spaces. These spaces exist on the borders of neurotypical experience and are here termed liminal - their character is fully investigated, and the authors determine that in their own excavations into these joint territories. They find evidence for the requirements for true engagement and connection with neurological difference, including technological access (meaning the absence of real time obstacles), a willingness to step into new and challenging spaces on the part of others, and egalitarian values at an interpersonal level. Object art, the absence of real time contact and mutual respect in this very particular case are seen to open up a World Behind the World.